Oxalate promoted iron dissolution of hematite via proton coupled electron transfer. Issue 5 (29th March 2022) - Zhan, Guangming; Fang, Yumin; Zhang, Meng; Cao, Shiyu; Xu, Tianyuan; Ling, Cancan; Gu, Huayu; Liu, Xiao; Zhang, Lizhi
Abstract : Oxalate promoted iron dissolution of hematite via proton coupled electron transfer. Abstract : Oxalate, a typical natural ligand, plays a significant role in promoting iron dissolution from iron (oxyhydr)oxide minerals to improve iron bioavailability in nature. However, the mechanism of oxalate promoted iron dissolution remains obscure due to the complicated interactions between oxalate and iron (oxyhydr)oxide minerals. Herein, oxalate promoted iron dissolution of hematite {001} nanoplates was examined at a molecular level with in situ attenuated total reflectance-Fourier transform infrared reflection (ATR-FTIR) spectroscopy, open circuit potential, H/D exchange experiments, and density functional theory (DFT) simulations. The results revealed that oxalate (C2 O4 2− ) would be gradually protonated with decreasing pH from 6.0 to 2.0, and then its protonated form (HC2 O4 − ) was adsorbed on hematite in a deprotonated bidentate mononuclear configuration, accompanied with the proton transfer from HC2 O4 − to the surface hydroxyl groups of hematite via a proton coupled electron transfer (PCET) mechanism during the adsorption to increase the acidity of the hematite surface, along with the injection of 0.65 electrons from the adsorbed C2 O4 2− into the bonded iron atom. Subsequently, the strength of Fe–O bonds on the hematite surface decreased to the same level as that of Fe(iii )·H2 O cluster formed between homogeneous Fe(iii ) and H2 O, as followed with the breakage of these weakened Fe–O bonds on the hematite surface, resulting in the final iron dissolution as Fe(C2 O4 )(H2 O) clusters from the hematite surface into solution. This study clarifies the intrinsic mechanism of oxalate promoted iron dissolution of hematite, and also sheds light on the iron dissolution of iron (oxyhydr)oxide minerals promoted by natural ligands.